Pengaruh Kepuasan Kerja Dan Keterlibatan Karyawan Terhadap Kinerja Karyawan Hotel KR Palembang - Mohammad Kurniawan Darma Putra (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to determine whether there is an influence between job satisfaction and employee involvement on employee performance at Hotel KR Palembang. The number of samples in this study amounted to 30 employees. The data collection technique in this study was by means of a questionnaire. Data were analyzed using multiple linear regression analysis model. Based on the test results with SPSS between job satisfaction (X1) and employee performance (Y) the t count is 17,581 > t table 2,055 which has a significant effect so that partially there is an influence between job satisfaction (X1) on employee performance (Y) the test results with SPSS between employee involvement (X2) on employee performance (Y) obtained the t count is 4.609 > t table 2.055 which has a significant effect, so that partially there is an influence between employee involvement (X2) on employee performance (Y). The results of the SPSS test between job satisfaction and employee involvement on employee performance obtained the number f count 100.856 > f table 3.35 which has a significant effect so that simultaneously there is an influence between the variables of job satisfaction and employee involvement on employee performance.